Determining the optimal nitrogen rate: N credits, soil tests, and crop‐based diagnosis. Issue 2 (30th March 2015) - Scharf, Peter C.
Abstract : This article, adapted from the new book, Managing Nitrogen in Crop Production, discusses three approaches for diagnosing optimal nitrogen rate: Nitrogen credits, soil tests, and crop‐based diagnosis. For more information on other approaches as well as many other topics related to N management, check out the book at https://dl.sciencesocieties.org/publications/books . Earn 1.5 CEUs in Nutrient Management by reading this article and completing the quiz at www.certifiedcropadviser.org/certifications/self‐study/703 .